Professional education of the nurse and ethical challenges of the profession - Barlem, Edison Luiz Devos (2014)
Nursing is characterized as a moral practice due to the constant need of taking decisions and making ethical choices, which involve the respect to the rights and the guarantee of the autonomy of the patients, not always identified that their actions or omissions result in significant impact to those with whom the care is developed. There are many factors which make these choices difficult, such as values in conflict or feelings of impotence facing the non-consistent actions with his own consciousness, showing that within the practice of care, the moral motivation is not the only determinant of the actions.